PENGUJIAN KUAT TEKAN BETON TERHADAP PENGGUNAAN CANGKANG KEMIRI PADA BETON RAMAH LINGKUNGAN - Johan Oberlyn Simanjuntak; Tiurma Elita Saragi; Nurvita Insani Simanjuntak; Imesari Hulu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2021)
One of the factors of economic growth is the development of infrastructure to encourage the creation of various activities. Concrete becomes an important part in the process of infrastructure development. For the concrete mixture, gravel is the most important part for concrete constituents. The limitation of gravel in nature led to the creation of various studies to replacement solutions for the use of gracel in concrete mixtures.Candlenut shell is one of the waste is not getting attention in its uses. Department of Plantation North Sumatera Province recorded the candlenut production in North Sumatera in 2019 reached 13,529.40 tons. The study aims for replace some of the gravel in the concrete mixture by using a candle nut shell. The variety of concrete mixture with candle nut is 10%, 20% and 30%. Testing was conducted on concrete ages 7 days, 14 days, 21 days and 28 days aimed at finding the difference between normal concrete compressive strength without additional candlenut shells and concrete with additional candlenut shells. The result shows that there was a decrease in the values of concrete compressive strength for each group of test objects. The decrease is due to the candlenut shell having higher and water absorption compared to gravel.